Egypt Public Land Management Strategy : Volume 2. Background Notes on Access to Public Land by Investment Sector--Industry, Tourism, Agriculture, and Real Estate Development - World Bank (Washington, DC, 2014)
The main objective of the Egypt Public Land Management Strategy is to provide the Government of Egypt (GOE) with practical and politically feasible policy recommendations to reform existing public land management policies and practices in the aim of improving the business climate in Egypt. This study is presented in two volumes: Volume one with the main policy note, supported by Volume two with background notes on access to public land by investment sector. Volume one examines the overall system for public land management in Egypt and the challenges facing investors seeking to access public land for investment projects, and concludes with a roadmap for public land management reform in the aim of improving the investment climate, which has been prepared in consultation with key government stakeholders. Volume two provides background notes examining the sectoral issues and challenges facing investors in terms of access to public land and development controls for four investment sectors: (i) industrial/manufacturing (updating the Policy Note prepared in December 2004 for the Egypt ICA); (ii) tourism; (iii) agriculture and land reclamation; and (iv) real estate development (i.e. large mixed used development projects involving a land subdivision process). This assignment focuses on public land management in Egypt, one of several interrelated land sector issues that merit in-depth examination. This study is intended to prepare the groundwork for the GOE to launch the process for formulating a public land management policy document, which would include the key policy objectives and principles for effective management of public land assets in Egypt and which would serve as a foundation to guide the process of reforming the fragmented legal framework governing public land management in Egypt. The process for public land asset management policy and legal reform is discussed in detail in this Policy Note.